Purification of river water through a bar sediment of riverbed - Tanaka, Yoshinori (Journal of Nepal Geological Society, 2000)
Changes in nitrogen components in river water were investigated for one sediment bar over three years. The plane distribution of water quality in the bar was investigated by sampling and measuring the water that lies just below the seepage water table in the bar. It was found that total nitrogen in the seepage water decreased downstream. The observed distribution patterns of nitrogen components are in agreement with the distributions of the dissolved oxygen and the oxidation and reduction potential in the seepage water. The nitrogen distribution patterns match the direction of seepage flow estimated from the seepage water level, indicating that the denitrification process decreased the nitrogen components in the river water as it passed through the bar sediment. A remarkable change in nitrogen components occurs at the shallow and actively flowing part on the upstream side of the bar due to the coexistence of oxidation and reduction around the seepage water table in the bar sediment. The removal efficiency of nitrogen per unit time is small in the individual bar. However, since several bars are present in the river and since the sediment below the river flow works in the same way as that in the bar, river sediment is thought to contribute greatly to the purification of river water. Thus, the present study has revealed that the natural water purification properties of river sediment, based on river sedimentology, should be used to reduce the pollution in urban and suburban rivers.